El Excentrico, 1966-02-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
February 05, 1966 [5 de enero de 1966]. Ano 16, No 8. Cover has a group photograph of people planing the 19th Annual United Food Drive. The talent show took place on February 25th at the Azteca Hall from 7 to 10 PM. The Dance took place on the following Sunday at the I.E.S. Hall from 2 to 10 PM. Admission price for these events is a donation of money or food cans.